The readiness of construction contractors and consultants to adopt e-tendering: The case of Sri Lanka. Issue 3 (11th April 2018) - Wimalasena, Nipuni Nilakshini; Gunatilake, Sachie
Abstract : Purpose: Tendering is a process undertaken to obtain offers from interested contractors to carry out specific packages of construction work. Presently, most construction stakeholders in developing countries use a paper-based tendering method, which is time-consuming, costly and labour-intensive. It may be argued that considering increased calls towards efficiency improvements in the construction industry, adopting e-tendering can bring about several benefits by allowing electronic exchange of information and avoiding the errors of traditional tendering. However, the question of readiness of construction stakeholders to embrace this change remains. The aim of this study is to investigate the readiness of Sri Lankan construction contractors and consultants (who are the two key parties involved in the tendering process) to adopt e-tendering. Design/methodology/approach: A mixed-methods research approach was used to achieve the aim. Initially, a literature review was used to compare typical conventional and e-tendering processes. Subsequently, a questionnaire survey was conducted to identify the current level of usage of e-tendering and to investigate the readiness levels of consultants and contractors to implement e-tendering. Finally, seven expert interviews were conducted to propose suitable solutions to achieve a successful e-tendering implementation. Findings: The analysed data revealed that both consultants and contractors used electronic media in the tendering process but they were still not ready for complete e-tendering implementation. However, consultants were more hesitant than contractors. The main barrier that limited e-tendering implementation was the lack of legal rules to cover e-tendering. Originality/value: E-tendering implementation should be initiated from the government sector. Therefore, it is recommended to update the procurement guideline and required legal policies to enrich the current usage level of e-tendering among construction stakeholders.